A Riemann invariant solver for mixture equations of compressible flows - Kolluru, Ramesh; Zeidan, Dia (AIP conference proceedings, 2023)
Numerical simulations of one-dimensional two-phase flow mixture of gas-liquid mixture is presented. The model consid-ers the relative velocity between the gas-liquid phases and is based on conservation equations for gas-liquid mixtures. The mixture model involves balance equations for the relative velocity and entropy with out source terms and are hyperbolic in nature. The gov-erning equations are solved in cell centred finite volume frame work with a newly developed central solver based on Generalised Riemann Invariants (GRI). The resulting first order scheme Riemann Invariant based Contact-discontinuity capturing algorithm (RICCA) is used with one dimensional governing equations for the numerical simulations. Higher order of accuracy is obtained using Vanleer based limiter reconstruction procedure and using WENO 3O reconstruction without any loss of generality. Solutions obtained using the algorithms agree well with those in the literature.